Delivering Team-Based Primary Care for the Management of Chronic Low Back Pain: An Interpretive Description Qualitative Study of Healthcare Provider Perspectives - Kyle Vader; Catherine Donnelly; Therese Lane; Gillian Newman; Dean A. Tripp; Jordan Miller (Taylor & Francis Group, 2023)
ABSTRACTBackground Chronic low back pain (LBP) is a prevalent and disabling health issue. Team-based models of primary care are ideally positioned to provide comprehensive care for patients with chronic LBP. A better understanding of primary care team perspectives can inform future efforts to improve how team-based care is provided for patients with chronic LBP in this practice setting.Aims The aim of this study was to understand health care providers' experiences, perceived barriers and facilitators, and recommendations when providing team-based primary care for the management of chronic LBP.Methods We conducted an interpretive description qualitative study based on focus group discussions with health care providers from team-based primary care settings in Ontario, Canada. Data were analyzed using thematic analysis.Results We conducted five focus groups with five different primary care teams, including a total of 31 health care providers. We constructed four themes (each with subthemes) related to experiences, perceived barriers and facilitators, and recommendations to providing team-based primary care for the management of chronic LBP, including (1) care pathways and models of service delivery, (2) team processes and organization, (3) team culture and environment, and (4) patient needs and readiness.Conclusions Primary care teams are implementing diverse care pathways and models of service delivery for the management of patients with chronic LBP, which can be influenced by patient, team, and organizational factors. Results have potential implications for future research and practice innovations to improve how team-based primary care is delivered for patients with chronic LBP.